Microsatellite instability in rectal cancer: what does it mean? A study of two randomized trials and a systematic review of the literature. Issue 3 (14th July 2022) - Swets, Marloes; Graham Martinez, Cristina; van Vliet, Shannon; van Tilburg, Arjan; Gelderblom, Hans; Marijnen, Corrie A M; van de Velde, Cornelis J H; Nagtegaal, Iris D
Abstract : Aim: Currently, compelling evidence illustrates the significance of determining microsatellite instability (MSI) in colorectal cancer (CRC). The association of MSI with proximal CRC is well established, however, its implications in patients with rectal cancer remain undefined. We therefore aimed to determine the role of MSI with respect to incidence and outcome in patients with rectal cancer. Methods and Results: For this we examined patients from two prospective phase III trials: TME trial and PROCTOR‐SCRIPT trial ( n = 1250). In addition, we performed a literature review to evaluate the overall prevalence, the effect on survival and the response to neo‐adjuvant treatment in patients with MSI rectal cancer compared with microsatellite stable (MSS) rectal cancer. Our TME and PROCTOR‐SCRIPT cohort showed no differences in terms of overall survival (OS) (hazard ratio [HR] 1.00, 95% confidence interval [CI] 0.69–1.47) and disease‐free survival (DFS) (HR 1.00, 95% CI 0.68–1.45) in patients with MSI compared to MSS rectal cancer. The total number of MSI cases in all included studies (including our own) was 1220 (out of 16, 526 rectal cancer patients), with an overall prevalence of 6.7% (standard error 1.19%). Both for OS as for DFS there was no impact of MSI status on prognosis (HR 1.00, 95% CI 0.77–1.29 and HR 0.86, 95% CI 0.60–1.22, respectively). The risk ratio (RR) for downstaging and pathological complete response showed also no impact of MSI status (RR 1.15, 95% CI 0.86–1.55 and RR 0.81, 95% CI 0.54–1.22, respectively). Conclusion: Rectal cancer patients with MSI form a distinct and rare subcategory, however, there is no prognostic effect of MSI in rectal cancer patients. Abstract : The role of MSI in rectal cancer.